2020
DOI: 10.14740/jocmr4108
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Cardiopulmonary Resuscitation of Patients With Human Immunodeficiency Virus Infection: A Population-Based Cohort Study of Epidemiology and Outcomes

Abstract: Background: Marked improvements were realized in both shortterm and long-term outcomes of human immunodeficiency virus (HIV)-infected patients following the introduction of combination antiretroviral therapy. However, the contemporary population-level patterns of in-hospital cardiopulmonary resuscitation (CPR) and the outcomes of HIV-infected patients were not systematically examined. Methods:We used the Texas Inpatient Public Use Data File to identify hospitalizations aged ≥ 18 years with and without HIV duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…A similar study by Lavi Oud reported that the incidence of ICPR was similar among those hospitalized with and without HIV infection; however, HIV-infected patients have been shown to have lower short-term survival rates in the United States [ 13 ]. In terms of short-term survival outcomes, Oud reported findings similar to those of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study by Lavi Oud reported that the incidence of ICPR was similar among those hospitalized with and without HIV infection; however, HIV-infected patients have been shown to have lower short-term survival rates in the United States [ 13 ]. In terms of short-term survival outcomes, Oud reported findings similar to those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of short-term survival outcomes, Oud reported findings similar to those of our study. Oud analyzed 437 and 54 135 patients with and without HIV, respectively, who experienced ICPR during hospitalization in the United States [ 13 ], while we analyzed 586 and 298 090 subjects in the PWH group and the control group, respectively, who experienced ICPR during hospitalization in South Korea. The findings from our study and those of Lavi Oud contradict those of a previous study by Mongardon et al, which reported that ICU mortality after cardiac arrest was not significantly affected by HIV infection among 99 patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation